THE INFLUENCE OF ENVIRONMENTALLY SOUND PRINCIPAL MANAGEMENT ON IMPROVING THE QUALITY OF SD NEGERI 1 PANDOWAN KAPANEWON OF GALUR - Sudariyah Sudariyah (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
The lack of maximum environmental management and low academic and non-academic achievement are real impacts that occurred at SD Negeri 1 Pandowan due to the implementation of environmental-based school management.  This study aims to describe how the principal’s management of environmentally sound improves the quality of education at SD Negeri 1 Pandowan. This research method is qualitative research with a phenomenological approach.   This study resulted in the management of environmentally sound principals implemented at SD Negeri 1 Pandowan having a positive impact on improving school quality, indicated by increasing academic scores and increasing school rankings on USBN activities at the sub-district level for several years. Meanwhile, non-academic scores have been shown by the championships at the kapanewon and district levels.  The impact of implementing environmentally sound principal management for teachers/schools is increased relation and cooperation among school residents, community, teacher’s creativity in learning, and leading to a school environment that becomes clean, beautiful, cool, no flood, the achievement of championship and contest in regional and sub-district level. In addition, the community’s trust in a local school is increased, which is seen from parents’ interest in sending their children to SD Negeri 1 Pandowan. Also, material and non-material aids are inclined as well as among stakeholders build harmonious relations.